Gold nanoparticle patterning on monomolecular chemical templates fabricated by irradiation-promoted exchange reaction - Zhao, Jianli; Terfort, Andreas; Zharnikov, Michael (The journal of physical chemistry. C, Energy, materials, and catalysis, 2011)
By use of custom-synthesized, citrate-passivated gold nanoparticles (NPs) as a test system, we have demonstrated a new approach to fabricate high-contrast and high resolution patterns of metal NPs. The patterns were fabricated on monomolecular chemical templates prepared by irradiation-promoted exchange reaction (IPER) lithography. The latter technique allows to introduce molecules bearing NP-binding tail groups into the selected areas of the primary NP-inert matrix, resulting in the desired chemical template. The advantages of the approach are (i) high flexibility in terms of the interfacial chemistry, length scale, and pattern form, (ii) low irradiation dose required for the primary patterning, and (iii) the possibility to use commercial molecules. The suggested strategy relies on strong electrostatic or covalent bonding of the NPs to the preselected functional groups, as was directly demonstrated for some of the target systems. A further important point is that the adsorption of the NPs does not affect the monolayer structure significantly, suggesting the persistence of the electronic structure of the film and NP-bearing molecules in particular, which can be of importance for applications in different areas such as sensor fabrication or nanoengineering.
Gesehen am 19.01.2023